Environmental Ethics in Tim Winton’s Shallows - Anne Alice R.J,; Dr. E. Anita, (The Bioscan, 2026)
Tim Winton’s debut novel,Shallows (1984), winner of the Miles Franklin Award, stands as a seminal work in Australian ecological literature, offering a profound critique of environmental exploitation and human greed. Set in the fictional Western Australian town of Angelus—loosely based on the last operating whaling town of Albany—the novel explores the ethical implications of the brutal whaling industry, set against the backdrop of an emerging conservationist consciousness in the late 1970s. This abstract examines how Shallows challenges anthropocentric views, advocating for an ecocentric approach that recognizes the intrinsic value of non-human nature. The novel portrays Angelus as a community entirely defined by its historic, 150-year tradition of killing whales, where the “shallows” represent both the treacherous physical spaces where whales are driven to shore and the limited, shallow mindset of its inhabitants who commodify nature. Winton portrays the whaling industry as the culmination of materialist greed that ignores ecological health in favor of economic production. The graphic, evocative descriptions of whale butchery serve to disrupt the reader's complacency, highlighting the violation of a majestic species for commercial, often wasteful, purposes. A central tension in the novel is the conflict between the traditional whalers, who view the ocean solely as a resource, and a small group of environmental activists, the “Greenies”, who represent a shift in environmental ethics. Queenie Cookson, a pivotal character, embodies this shift; she struggles with her own ancestry as a descendant of whalers, choosing to defend the whales against her community and her husband, Cleve Cookson. Queenie’s journey highlights a burgeoning ecological consciousness, a “voice of nature” that challenges the “crimes of ancestors” and seeks a post-colonial, post-speciesist reconciliation with the land and sea.